Identification of potential inhibitors for mycobacterial uridine diphosphogalactofuranose-galactopyranose mutase enzyme: A novel drug target through in silico approach - Tapaswini Nayak; Lingaraja Jena; Pranita Waghmare; Bhaskar C Harinath (International Journal of Mycobacteriology, 2018)
Background: The Mycobacterium tuberculosis (MTB) uridine diphosphogalactofuranose (UDP)-galactopyranose mutase (UGM) is an essential flavoenzyme for mycobacterial viability and an important component of cell wall. It catalyzes the interconversion of UDP-galactopyranose into UDP-galactofuranose, a key building block for cell wall construction, essential for linking the peptidoglycan and mycolic acid cell wall layers in MTB through a 2-keto intermediate. Further, as this enzyme is not present in humans, it is an excellent therapeutic target for MTB. Thus, inhibition of this UGM enzyme is a good approach to explore new anti-TB drug. This study aims to find novel and effective inhibitors against UGM from reported natural phytochemicals and ZINC database using virtual screening approach. Methods: In this study, 148 phytochemicals with reported antitubercular activity and 5280 ZINC compounds with 70% structural similarity with the natural substrate of UGM (UDP-galactopyranose and UDP-galactofuranose) were screened against UGM. Results: In virtual screening, 19 phytochemicals and 477 ZINC compounds showed comparatively better binding affinity than natural substrates. Among them, best 10 compounds from each group were proposed as potential inhibitors for UGM based on the binding energy and protein-ligand interaction analysis. Among phytochemicals, three compounds, namely, tiliacorine, amentoflavone, and 2'-nortiliacorinine showed highest binding affinity (binding energy of −10.5, −10.4, and −10.3 Kcal/mol, respectively), while among ZINC compounds, ZINC08219848 and ZINC08217649, showing highest binding affinity (binding energy of −10.0 and −9.7 Kcal/mol, respectively) toward UGM as compared to its substrates. Conclusion: These selected compounds may be proposed as potential inhibitors of UGM and need to be tested in TB culture studies in vitro to assess their anti-TB activity.